Application and theory of petri nets and concurrency : 34th International Conference, PETRI NETS 2013, Milan, Italy, June 24-28, 2013. Proceedings - Desel, Jorg; Colom, Jose-Manuel (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 34th International Conference on Applications and Theory of Petri Nets and Concurrency, PETRI NETS 2013, held in Milan, Italy, in June 2013. The 18 regular papers and 2 tool papers presented were carefully reviewed and selected from 56 submissions. The book also contains 2 invited talks. All current issues on research and development in the area of Petri nets and related models of concurrent systems are addressed.